RISK FACTORS OF MAJOR CARDIOVASCULAR EVENTS IN LONG-TERM PERIOD OF CORONARY BYPASS IN PATIENTS WITH ISCHEMIC HEART DISEASE AND 2ND TYPE DIABETES MELLITUS - A. N. Sumin; N. A. Bezdenezhnykh; A. V. Bezdenezhnykh; S. V. Ivanov; O. L. Barbarash (Российский кардиологический журнал)
Aim. To reveal the risk factors of major cardiovascular events (MCVE) in long-term period after CABG with DM2.Material and methods. Prospective study of 324 patients with CHD after CABG. Patients were selected into 2 groups: 148 with DM2 (median age 58 y., median of long-term follow-up 1,8 y.), 176 patients without DM and another disorders of carbohydrate metabolism (median age — 58 y., median follow-up 1,7 y.). As the long-term MCVE we used MI, stroke, cardiovascular death. An estimation of the freedom from MCVE was done by the method of multiplying estimations by KaplanMeier. To reveal risk factors for MCVE we used logistic regression.Results. Patients of both groups were comparable by the age (p=0,211), long-term outcome follow-up (p=0,132). Patients with DM2 had more often the MCVE (14,2% and 6,3%, respectively, p=0,028). By the Kaplan-Meier method we built the curves of the freedom from MCVE in the studied groups, with the test of Gekhan-Wilkokson we found differences (p=0,013). MCVE in long-term period after CABG was found in 4 patients with DM (2,7%) and in two — without DM (1,1%), p=0,529. By the results of multifactor analysis as the predictors for MCVE were DM2 (OR 3,30795% CI 1,372-7,968, р=0,007), female gender (OR 2,75295% CI 1,074-7,049, р=0,034), not related to age or renal function. Chance of MCVE in long-term period increased with the time of on-pump (OR 1,14595% CI 1,024-1,280, р=0,016 ) and with the decrease of LV EF (OR 1,04395% CI 1,001-1,087, р=0,041) with the presence of peripheral atherosclerosis the risk of long-term MCVE increased 5,5 times (OR 5,53995% CI 1,564-19,620, р=0,007) not related to gender, age, LV EF, GFR or statin intake. The level of fasting glucose at the moment of admittance after CABG was an independent predictor for MCVE (OR 1,144, р=0,037).Conclusion. The independent predictors of MCVE in long-term post-CABG period are DM2, female gender, peripheral atherosclerosis, duration of on-pump period, EF LV and glycemia before operation.